Efficacy of new herbicide on weeds and profitability of spring planted sugarcane (Saccharum officinarum) under subtropical Indian condition - CHOUDHARY, H R; SINGH, R K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted to effect of sequential application of herbicide on weeds in spring planted sugarcane (Saccharum officinarum L.) during the spring seasons of 2011-12 and 2012-13 at the Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, Uttar Pradesh, India. Results clearly revealed that weed biomass at 90 DAP, weed control efficiency at 90 DAP, weed index and cane yield (132.43 tonnes/ha in 2011-12 and 138.21 tonnes/ha in 2012-13) were significantly with conventional practice (Three hoeings) at 30, 60 and 90 DAP. However, the conventional practice (Three hoeings) at 30, 60 and 90 DAP significantly increased the profitability of sugarcane such as cost of cultivation, gross return, net return and B:C ratio (2.96 and 3.13 in 2011-12 and 2012-13, respectively) and second best treatment was sequential application of ametryne @ 2.4 kg a.i./ha at 30 DAP fb 2,4-D @ 1.0 kg a.i./ha at 60 DAP of sugarcane.